Oral hygiene status, gingival status, periodontal status, and treatment needs among pregnant and nonpregnant women: A comparative study - Meena Kashetty; Sagar Kumbhar; Smita Patil; Prashant Patil (Journal of Indian Society of Periodontology, 2018)
Objectives: The gingival and periodontal changes during pregnancy are well known. Gingivitis is the most prevalent oral manifestations associated with pregnancy. The hormonal and vascular changes that accompany pregnancy are known to exaggerate the inflammatory response to the local irritants. Hence, a study was designed to assess oral hygiene status, gingival status, periodontal status, and treatment needs (TNs) among pregnant and nonpregnant women. Materials and Methods: A cross-sectional study was conducted among 120 pregnant and 120 nonpregnant women of 18–44 years age attending the Outpatient Department of Gynaecology and Obstetrics in Government Hospital of Belgaum city, Karnataka, India. The study consisted of an interview and oral examination. Type 3 examination was followed. Simplified Oral Hygiene Index (OHI-S), Gingival Index, and Community Periodontal Index and TNs Index were used to assess “oral hygiene status,” “gingival status,” and “periodontal status and TNs,” respectively. Results: The pregnant women showed poor oral hygiene with the mean OHI-S score as 2.68. Gingivitis was prevalent in almost all the pregnant and nonpregnant women. However, it was found more severe in pregnant women with mean gingival score as 1.25. A definite increase in gingivitis was found from Trimester II to Trimester III. The mean number of sextants showing healthy gingiva was significantly (P < 0.01) lower among pregnant women. Conclusions: Pregnant women showed poor oral hygiene, more gingival inflammation, and more periodontal disease as compared to nonpregnant women. The severity of gingivitis increased in Trimester III. Proper oral hygiene practice can prevent these diseases and further complications.